PELAYANAN PUBLIK MELALUI PENERAPAN APLIKASI SICANTIK MENUJU E-GOVERNMENT PADA DINAS PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU SATU PINTU KABUPATEN KOLAKA TIMUR - Darwan Sari; Yunitawati Lampasa; Murniati; Nasruddin (Halu Oleo University, 2023)
The research aims to analyze the effectiveness of public services through the application of the e-Government of the Investment Office and One Stop Integrated Licensing Service, East Kolaka Regency. The study is done using descriptive qualitative research, by taking 8 informants with related positions. The results of the study show that the DPMPTSP of East Kolaka Regency has been carrying out existing related regulations to provide public services and ensuring it follows service operational standards. The constraints of public service effectiveness and delivery process are caused by the lack of infrastructure and facilities due to the regional budget. The obstacles to the SICANTIK application are the lack of community capability in terms of technology and the constraint of the internet network. Optimizing e-government through public service standards according to the East Kolaka Regency regional regulation number 16 of 2018 is considered good because the service is carried out based on SOPs. However, there are still shortcomings in terms of personnel competence, communication infrastructure, community readiness, and limited capital.